Examining Pathways from Food Insecurity to Safer Sex Efficacy Among Northern and Indigenous Adolescents in the Northwest Territories, Canada - Logie, Carmen H.; Lys, Candice; Sokolovic, Nina; Malama, Kalonde; Mackay, Kayley Inuksuk; McNamee, Clara; Lad, Anoushka; Kanbari, Amanda (International Journal of Behavioral Medicine, 2024)
Background Food insecurity is a social determinant of health linked with elevated HIV exposure. Safer sex efficacy (SSE), the ability to navigate sexual decision-making and condom use, is an important marker of sexual wellbeing. Pathways from food insecurity to SSE are understudied, particularly among adolescents in Arctic regions who are at the nexus of food insecurity and sexual health disparities. We examined pathways from food insecurity to SSE among adolescents in the Northwest Territories (NWT), Canada. Methods We implemented cross-sectional surveys with adolescents aged 13–18 recruited through venue-based sampling in 17 NWT communities. We conducted multivariable logistic regression to assess socio-demographic factors associated with food insecurity. We then conducted structural equation modeling (SEM) using maximum likelihood estimation to assess direct effects of food insecurity on SSE and indirect effects via resilience, depression, and relationship power inequity. We assessed both condom use SSE (e.g., confidence in using condoms) and situational SSE (e.g., SSE under partner pressure). Results Most participants ( n = 410) identified as Indigenous (79%) and 45% reported experiencing food insecurity. In SEM, we did not find a significant direct effect from food insecurity to SSE; however, we found indirect effects from food insecurity to condom use SSE through resilience and depression and from food insecurity to situational SSE through resilience. Conclusions Findings call for structural interventions to address food insecurity, alongside resilience-focused strategies that address the intersection of sexual and mental health. Sexual health strategies focused on individual behavior change are insufficient to address larger contexts of poverty among Northern youth.